Edge-Interior Disparities in Tree Species and Structural Composition of the Kilengwe Forest in Morogoro Region, Tanzania. (26th March 2014) - Kacholi, David Sylvester
Abstract : A survey to determine the variation in species and structural composition of trees along the edge-interior gradient was done in the Kilengwe forest in Morogoro region, Tanzania. The forest was categorized into three habitats, namely, edge (0–100 m), intermediate (100–200 m), and interior (>200 m) depending on the distance from the forest margin. A total of six plots of 0.04 ha each were randomly placed in each of the habitats whereby all trees with DBH ≥ 10 cm were inventoried. A total of 67 species representing 26 families were recorded. Fabaceae was the most speciose and abundant family. Brachystegia spiciformis was the most abundant species. Of the recorded species, 10.45% were common in the three habitats while 8.95%, 13.43%, and 26.86% occurred exclusively to the edge, intermediate, and interior habitats, respectively. The forest interior was significantly rich in terms of species richness, diversity, density, and basal area than the edge and intermediate habitats. The edge had significantly higher number of stumps/ha. In summary, the results suggest that edge/intermediate and interior are contrasting habitats in terms of tree species richness, diversity, and structural composition. Moreover, the forest edge and intermediate habitats were found to be characterized by high anthropogenic activities compared to the forest interior habitat.